The Neolithic Transition and the Genetics of Populations in Europe - ALBERT J. AMMERMAN, LUIGI LUCA CAVALLI-SFORZA (Princeton University Press, 2014)
The aim of this book is to bring together and provide an overview of the various studies that we have undertaken over the last twelve years on the shift from hunting and gathering to early farming as a new way of life in Europe and the implications of the neolithic transition for the genetic structure of human populations in Europe. One of the challenges that we have had to face in writing the book involves the range of academic backgrounds that different readers are likely to possess. On one hand, there is the need to present archaeological material to those whose training and experience are primarily in human genetics and the biological sciences. On the other, concepts and quantitative methods used in human population genetics must be developed in a clear manner for those coming from backgrounds in archaeology and the social sciences. We have thus tried to concentrate on the larger picture in the body of the text and to place more technical material and points of interest to specialists in notes to the respective chapters. It is worth stressing at the outset that the chapters of the book dealing specifically with the neolithic transition are not written as a "prehistory" in the traditional sense of the term: that is, the fashioning of a narrative that attempts to portray diverse facets of the early life of a given region or period. Rather, we have adopted a more limited and thematic focus, essentially that of outlining what is currently known about the origins of early farming in Europe. Readers who become interested in more detailed regional studies may find it useful to consult the references listed in the bibliography. Another point that needs to be made here is that our current knowledge of neolithic sites in most parts of Europe is still quite limited. Moreover, the nature of what is known is often dependent on when and how archaeological fieldwork was conducted. We can fully expect our understanding of the neolithic transition in Europe to increase substantially as further fieldwork is done over the next twenty-five years. Our own experience working at early neolithic sites in the region of Calabria in southern Italy, which is described elsewhere, offers a good example of how rapidly our knowledge of an area can change once intensive research is initiated. On a more technical note, radiocarbon dates are cited throughout the book in conventional C-14 years and not calibrated ones, since the calibration curves available at the present time (see Chapter 4) extend back only to about 7000 B.P. and do not cover the full time range of our study.